2006
DOI: 10.1080/09540120500101625
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the JEWEL project: An innovative economic enhancement and HIV prevention intervention study targeting drug using women involved in prostitution

Abstract: The JEWEL (Jewellery Education for Women Empowering Their Lives) pilot study examined the efficacy of an economic empowerment and HIV prevention intervention targeting illicit drug-using women (n=50) who were involved in prostitution in Baltimore, Maryland. The intervention was comprised of six 2-hour sessions that taught HIV prevention risk reduction and the making, marketing and selling of jewellery. Bivariate comparisons examined behaviour change pre- and 3-months post-intervention. The intervention's effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
149
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 58 publications
7
149
1
5
Order By: Relevance
“…It is important that policy makers recognize these realities and balance the perceived benefits of criminal-prohibition with other associated outcomes, such as increased levels of crime and IDU engagement in risky prohibited income generating activities While this analysis suggests that higher intensity addiction and the costs associated with purchasing illegal drugs are central factors influencing active IDU to engage in prohibited income generating activities, the lack of available alternative income sources is also an important aspect of this relationship. Many active IDU have difficulty finding sufficient legitimate paid work due in part to unstable housing, limited employable skills and low levels of education (Sherman et al, 2006). One alternative for these individuals is to obtain income assistance and other forms of social assistance; however, income analysis in the present study found the median income from social assistance to be $800, which for most IDU is insufficient to support a secure living and habitual drug consumption (Casavant and Collin, 2001;Fischer et al, 1999).…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…It is important that policy makers recognize these realities and balance the perceived benefits of criminal-prohibition with other associated outcomes, such as increased levels of crime and IDU engagement in risky prohibited income generating activities While this analysis suggests that higher intensity addiction and the costs associated with purchasing illegal drugs are central factors influencing active IDU to engage in prohibited income generating activities, the lack of available alternative income sources is also an important aspect of this relationship. Many active IDU have difficulty finding sufficient legitimate paid work due in part to unstable housing, limited employable skills and low levels of education (Sherman et al, 2006). One alternative for these individuals is to obtain income assistance and other forms of social assistance; however, income analysis in the present study found the median income from social assistance to be $800, which for most IDU is insufficient to support a secure living and habitual drug consumption (Casavant and Collin, 2001;Fischer et al, 1999).…”
Section: Discussioncontrasting
confidence: 46%
“…This would involve supporting the development of legitimate means of earning income through various low threshold employment opportunities and skill building measures. A recent intervention designed to economically empower drug addicted sex trade workers to develop alternative legitimate sources of income has been shown to have a positive influence on reducing involvement in the sex trade industry (Sherman et al, 2006). Alternatively, policy makers could intervene by providing addiction prescription and substitution therapies to individuals with markers of serious addiction to decrease their reliance on, and subsequent need to purchase, street drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negotiating power (i.e., safer sex communication, ability to insist on condom use, discussion of previous sexual partners) and economic independence were both associated with increased condom use. 50 These authors, along with promising results from an economic empowerment and HIV prevention intervention study with commercial sex workers in the USA, 51 indicate that empowering women through income-generating activities and negotiation skill building may influence safer sex behaviors. These findings and others suggest that structural-level interventions show potential to increase economic resources and decrease HIV/ AIDS risks, particularly for disenfranchised women.…”
Section: Discussionmentioning
confidence: 99%
“…That women's empowerment and other interventions that address the socioeconomic vulnerability of women may contribute to reductions in HIV risk behaviour is also emphasised in a study from South Africa (Pronyk et al, 2008c). In the US context economic empowerment programmes enabling women to earn income, resulted in reduction in sexual partners and as well as commercial sex (Sherman, German, Cheng, Marks & Bailey-Kloche, 2006). …”
Section: Discussionmentioning
confidence: 99%